Family as a Socio-economic Actor in the Political Economies of East and South East Asian Welfare Capitalisms - Papadopoulos, Theodoros; Roumpakis, Antonios (Social Policy & Administration, 2017)
In this article, we revisit Karl Polanyi's concept of 'oikos' in order to reconceptualize the role of the family as both a welfare provider and an economic actor in the social reproduction of East and South East Asian welfare capitalisms. Our article is structured in four parts. First, we critically review existing approaches on the characteristics of welfare capitalism in East and South East Asia. We argue that existing approaches tend to isolate family as a welfare provider and neglect how the role of the family is institutionalized as a collective actor. The second part focuses on the role of the family in the social reproduction of welfare capitalism, and explores how, in East and South East Asia, the specific conditions for family's role as an economic actor were institutionalized historically. The third part revisits Polanyi's concept of 'oikos' and how 'householding' constitutes one of the most important forms of economic action allowing us to examine the family as a socio-economic actor. In the fourth section, we provide an analysis of families' available strategies and discuss evidence related to private education expenditure, household debt and labour market income share. We conclude by highlighting the need to re-articulate the importance of family as a collective socio-economic actor that, despite recent reforms and path departures, remains at the epicentre of East and South East Asian welfare capitalisms.
Political Science; Public Administration
Keywords: East and South East Asia; OIKOS (The Greek word); debt; economic conditions in Asia; families & economics; family; households and economics; social reproduction; welfare capitalism; welfare state

Book Review Essay: The Environmental Crisis and Its Capitalist Roots: Reading Naomi Klein with Karl Polanyi*—Naomi Klein: This Changes Everything: Capitalism vs. the Climate - Adler, Paul S. (Administrative Science Quarterly, 2015)
An essay is presented on the relationship between climate change and capitalism, offering a reading of the argument in "This Changes Everything: Capitalism vs. the Climate" by Naomi Klein through the lens of the analysis in "The Great Transformation" by Karl Polanyi. The author suggests that Klein's argument is not clear on whether capitalism in any form or only the current, neoliberal version of capitalism is incompatible with effective action to address the problem of climate change. Topics include environmental externalities and policies addressing them, the environmental record of corporations, and the theory of the self-regulating market.
Business; Management Studies; Administrative Science
Keywords: Great Transformation; The (Book); KLEIN; Naomi; This Changes Everything (Book); business enterprises & the environment; capitalism; climatic changes; economic aspects; environmental policy; externalities

Mutating Neoliberalism: The Promotion of Italian Investors in Slovakia before and after the Global Financial Crisis - Sellar, Christian; Pástor, Rudolf (International Journal of Urban & Regional Research, 2015)
In the context of the literature on 'actually existing neoliberalisms', this article analyzes the policies and services supporting Italian foreign direct investment (FDI) in Slovakia. It identifies a group of organizations, both Slovak and Italian, which shape and deliver neoliberal pro-FDI policies. By studying such an 'investment promotion community' (IPC) before and after the global financial crisis of 2009, and during Italy's prolonged crisis, this article shows both the persistence and adaptability of neoliberal policies and institutions. In so doing, it highlights some of the transnational flows underpinning the 'domestication' of neoliberalism in Slovakia. These findings support recent literature arguing that post-crisis neoliberalism can be interpreted as a stunted Polanyian double movement, in which the state has improved some of its regulatory functions but without questioning the overarching neoliberal principles. Specifically, it shows that FDI policies and the support of Italian investors rest upon a professional community that has not changed much since the 2009 crisis. This community played a crucial role in embedding neoliberal rationalities in Slovakia and supports the persistence of this ideology in the post-crisis environment.
Political Science; Public Administration
Keywords: Bratislava; Italy; Košice; Kralovsky Chlmec; Slovakia; Slovakia - economic conditions; Slovakia - foreign economic relations; capitalists & financiers; double movement; financial crisis; foreign direct investment; foreign investments; global financial crisis; 2008-2009; neoliberalism

The political economy of public sector trade union militancy under Keynesianism: The case of local government - Gill-McLure, Whyeda (Capital & Class, 2013)
Public service labour’s distinctiveness is insufficiently understood or recognised; and in its ad hoc growth under liberal ideologies of state intervention (those of Mill and Keynes), it has been treated both as if it were and were not public service labour. This paper teases out some of the crucial links between liberal ideologies of state intervention and the social praxis of public service unionism, outlining the latter’s historical struggle against this paradoxical treatment, which culminated in 1970s militancy. The paper supports this argument with a Marxist analysis of public sector labour, drawing on Polanyi’s ‘double-movement’ to understand the limitations of liberal ideologies of state intervention.
Business; Public Administration
Keywords: Marxist analysis; civil service; distinctiveness of public service labour; double movement; ideology; labor process; labour process; liberalism; political economy; public sector union militancy